Dampak Perubahan Tataguna Lahan Terhadap Keseimbangan Air Wilayah Pulau Seram. Studi Kasus : Das Way Pia Di Kabupaten Maluku Tengah, Provinsi Maluku - Semuel Laimeheriwa (Agrologia, 2012)
This research was conducted to estimate the values of parameters which described the physical characteristics of catchments area and monthly water balance components, and understand the sensitivity of the water balance components to change in the parameter value due to the physical changes occurring in Way Pia catchments area, Ceram Island.  The method used involved calculation of the regional water balance in the current time (normal) and during the time of land use change, using an evapoclimatonomy model. The main model inputs were monthly rainfall, global radiation and run off. Analyses of data were conducted with five steps as follows : (1) mathematical formulation of the evapoclimatonomy model, (2) algorithm formation and transfer to computer code, (3) establishment of parameters and calibration, (4) validation of model, and (5) experimentation of model. The current physical conditions of Way Pia catchments area were characterized by: average of parameter value of albedo, a = 0,16; rainfall threshold, Pn = 100 mm; surface run off ratio, np = 0,23; evapority, ep = 0,42; measure of soil water loss from sub surface, vN = 0,12; and measure of evapotranspiration of soil water from sub surface, vE = 0,20. Model output of the current water balance consisted of  annual value of soil moisture, m = 272 mm; total evapotranspiration, E = 1393 mm, and total run off, N = 920 mm. The land use change  in the form of land clearing will increase the parameter values of a and np, which affect on increasing of direct run off (N') of 13% as compared to current conditions.